Effect of lithological and geotechnical characteristics on the generation of debris flows in the arid basin of Mirave, Peru - Bizarreta Ortega, Julio César (2022)
Studies concerning the debris flows in mountain areas are relevant because of their potential negative effects on the human communities and infrastructure in their areas of influence. To advance the understanding of the theoretical basis, this study qualitatively analyzes the effect of lithological characteristics and soil type on the generation of debris flows in the arid basin of Mirave, in southern Peru, as a consequence of extensive rainfall. Two debris flow events are evaluated, which occurred in the studied area in March 2015 and February 2019. The method used to achieve the objective combines the use of satellite images, field data collection, and lab tests results to estimate the relative importance of the abovementioned characteristics in the generation of debris flows. The results suggest that the poor presence of clay and the predominance of sandy-loamy structured soils in the Mirave Basin make them unstable when erosion occurs. In addition, the features of broken down materials generated from residual and colluvial soils in the primary area of study are one of the main causes of debris flows in the region.